Evaluating the Use of Alum Sludge in Treatment of Wastewater Effluent Case Study: Namatala Wastewater Stabilization Pond in Mbale - Susan Alungat (Uganda Christian University, 2024)
One of the final products for wastewater stabilization ponds is effluent discharged to the environment. And as well in raw water treatment, the key process for portable water treatment is clarification by use of Alum as a coagulant. This comprises of coagulation, flocculation and sedimentation to enhance the removal or the reduction of contaminates in water and in turn slurry Alum sludge is produced as waste product. The use of the alum sludge as an economic and sustainable way in treating the wastewater effluent to meet the discharge standards is key. The Alum sludge used in this work contained aluminum concentration of 15.81% obtained from 5g of dry Alum sludge dissolved in a solution of 100ml of 3N concentrated sulphuric acid hence making it a potential coagulant recovered suitable for reuse. The jar test gave the optimum dose of Alum extract of 35mg/l that reduced Turbidity by 82.3% from 39 NTU to 6.9 NTU at PH of 7.78. The optimum dose of the Alum extract applied to treat the wastewater effluent effectively reduced on the contaminates such as BOD, COD, Total Phosphorus and Total Nitrogen to meet the discharge standards from 202 ± 3.89mg/l to 41 ± 0.45 mg/l, 397 ± 2.59mg/l to 80 ± 1.86 mg/l, 73.4 ± 1.47mg/l to 9.1 ± 0.28 mg/l, and 51.4 ± 3.55 mg/l reduced to 3.7 ± 0.35 mg/l. Therefore, environmental friendly way of Alum recovery from the Alum Sludge to reuse as a coagulant in treating wastewater effluent gave economical and sustainable solution to protect the environment.